Semai children in Cameron Highland and understanding the indigenous childrens rights in international law / Mohamad Sabri Yusof and Dr. Mohd Kamal Azman Jusoh - Yusof, Mohamad Sabri; Azman Jusoh, Mohd Kamal (2015)
Adults and parents perceive that under the law they are having full authority to decide what is best for the children without realising that the children themselves also have rights to decide what is best for them. The same perception appears in the family circle of the Semai and other indigenous people in general. This paper tries to help adult and parents to understand the terms of some of the minimum rights provided to the children around the world including the indigenous children under International Law so that one is not caught unaware and help secure the very basic needs of children of today.